Coaching young in soccer: possibilities from a wavy model - Baggiotto-Bettega, O.; Rafaela-Galatti, L.; Ibáñez-Godoy, S.; Antunez-Medina, A.; José-Scaglia, A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2019)
The design of a youth athlete development process in soccer must be coherent with the major context, considering challenges and potentialities, and qualifying tactical-technical competences. Considering that, this theoretical study aims to present a “wavy model” for soccer, adapted from Ibáñez (2011), as a supporter for the organization and systematization of the tactical-technical defensive and offensive game phases, as much as insure the coaching and assessment process.